Modelling of natural convection along isothermal plates and in channels using diffusion velocity method (2010)
The diffusion velocity method (DVM), a version of vortex element method (VEM), was used to model the steady state, laminar natural convection flows along isothermal vertical plates and in isothermal vertical channels. For each case, numerical models were developed using DVM from the vorticity transport equation and the energy equation. This study shows that the diffusion velocity method is a viable numerical tool at modelling not only fluid flow problems but also the heat transfer problems.